2010
DOI: 10.1038/leu.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

A phase-2 trial of low-dose pomalidomide in myelofibrosis

Abstract: In a previous study, we reported on the safety and efficacy of low-dose (0.5 mg) pomalidomide and prednisone and pomalidomide alone (2 mg/day), for the treatment of anemia associated with myelofibrosis (MF). The current study examined the value of low-dose pomalidomide alone. The main eligibility criterion was transfusion-dependency or hemoglobin o10 gm per 100 ml. Anemia response was assessed by International Working Group criteria. Pomalidomide (0.5 mg/ day) was given to 58 patients (median age 68 years); 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 24 publications
0
85
0
3
Order By: Relevance
“…For example, more than half of the patients were symptomatically anemic (ie, hemoglobin Ͻ10 g/dL) at time of referral and 38% required red blood cell transfusions, underscoring the dire need for an antianemia drug in PMF. 37,38 The particular information also points out the limitations of drugs that display anemia as an adverse effect, which is a recurrent issue with certain JAK inhibitors. 24,25 The study also suggests that about a third of patients present with marked splenomegaly or constitutional symptoms and might, therefore, benefit from JAK inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, more than half of the patients were symptomatically anemic (ie, hemoglobin Ͻ10 g/dL) at time of referral and 38% required red blood cell transfusions, underscoring the dire need for an antianemia drug in PMF. 37,38 The particular information also points out the limitations of drugs that display anemia as an adverse effect, which is a recurrent issue with certain JAK inhibitors. 24,25 The study also suggests that about a third of patients present with marked splenomegaly or constitutional symptoms and might, therefore, benefit from JAK inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase-2 randomized study, pomalidomide alone at 2 mg/day was shown to be as active (23% response rate), in the treatment of anemia, as prednisone plus pomalidomide at 0.5 (36% response rate) or 2 mg/day (16% response rate) [4]. In an extension of the above-mentioned phase-1 study [15], low-dose pomalidomide (0.5 mg/day), as a single agent, was given to 58 patients and induced a 17% anemia response, which was predicted by the absence of marked splenomegaly, presence of JAK2V617F, and lower circulating levels of monocyte chemotactic protein-1, interleukin (IL)-2R, IL-15, and IL-8 [16]. Pomalidomide treatment was also beneficial in terms of alleviating thrombocytopenia but its effect on splenomegaly was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently communicated the short-term results of two consecutive clinical trials using pomalidomide therapy for MF [4,14,15]. The maximum tolerated dose of pomalidomide in MF was 3 mg/day (dose-limiting toxicity was myelosuppression) but doses higher than 2 mg/day were associated with more myelosuppression and other toxicities and were not necessarily more effective [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations